(untitled) (Revista da Universidade Federal de Minas Gerais, 2012)
This paper aims at understanding the relationships between the body and the city, and between dance and architecture. While these relations have been largely neglected in urbanism and cities historiography, our premise is that the body and the city are reciprocally shaped. The city is perceived by the body in a set of interactive conditions and the body expresses the synthesis of such interaction by means of what we call urban corpographia: a kind of bodily cartography that is formulated from the standpoint of the urban experience and is embodied by whoever experiences it. The study of corpographias can contribute to foster criticism upon the current process of aestheticization and spectacularization of culture and the city, of art and the body.